Elucidation of wave pressure acting on a wave-cut notch beneath a coastal cliff based on laboratory experiments and numerical modeling - Watanabe, Masashi (2023)
To investigate past extreme waves which deposited cliff-top boulders, it is important to elucidate the wave force acting on wave-cut notches beneath coastal cliffs. Our laboratory experiments have revealed that extreme waves over coastal cliffs generated both sustained and impulsive forces, and that sustained forces can be estimated from buoyancy, because velocities are rather small when sustained forces are generated. Thus, boulders at coastal cliffs are likely moved by impulsive forces but not by sustained forces. We have also proposed coefficients of the formula which can reproduce impulsive and sustained wave forces acting on the notch based on observed and simulated wave heights and velocities. Using the proposed formula, wave heights and velocities that are necessary to move boulders up coastal cliffs can be estimated without numerical simulations. In our future investigation, we will account for the scaling effect of impulsive forces acting on coastal cliffs.